Combining Phytate/Ca2+ Fractionation with Trichloroacetic Acid/Acetone Precipitation Improved Separation of Low-Abundant Proteins of Wheat (Triticum aestivum L.) Leaf for Proteomic Analysis - Muhammad ARF Sultan; Hui LIU; Yu-Feng CHENG; Pei-pei ZHANG; Hui-xian ZHAO (Journal of Integrative Agriculture, 2013)
Proteomic assessment of low-abundance leaf proteins is hindered by the large quantity of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) present within plant leaf tissues. In the present study, total proteins were extracted from wheat (Triticum aestivum L.) leaves by a conventional trichloroacetic acid (TCA)/acetone method and a protocol first developed in this work. Phytate/Ca2+ fractionation and TCA/acetone precipitation were combined to design an improved TCA/acetone method. The extracted proteins were analysed by two-dimensional gel electrophoresis (2-DE). The resulting 2-DE images were compared to reveal major differences. The results showed that large quantities of Rubisco were deleted from wheat leaf proteins prepared by the improved method. As many as (758±4) protein spots were detected from 2-DE images of protein extracts obtained by the improved method, 130 more than those detected by the TCA/acetone method. Further analysis indicated that more protein spots could be detected at regions of pI 4.00–4.99 and 6.50–7.00 in the improved method-based 2-DE images. Our findings indicated that the improved method is an efficient protein preparation protocol for separating low-abundance proteins in wheat leaf tissues by 2-DE analysis. The proposed protocol is simple, fast, inexpensive and also applicable to protein preparations of other plants.